1-point RANSAC for EKF-based Structure from Motion - Civera, J.; Grasa, O.G.; Davison, A.J.; Montiel, J.M.M. (2009 IEEE/RSJ International Conference on Intelligent Robots and Systems, 2009)
Recently, classical pairwise Structure From Motion (SfM) techniques have been combined with non-linear global optimization (Bundle Adjustment, BA) over a sliding window to recursively provide camera pose and feature location estimation from long image sequences. Normally called Visual Odometry, these algorithms are nowadays able to estimate with impressive accuracy trajectories of hundreds of meters; either from an image sequence (usually stereo) as the only input, or combining visual and propioceptive information from inertial sensors or wheel odometry. This paper has a double objective. First, we aim to illustrate for the first time how similar accuracy and trajectory length can be achieved by filtering-based visual SLAM methods. Specifically, a camera-centered Extended Kalman Filter is used here to process a monocular sequence as the only input, with 6DOF motion estimated. Features are kept live in the filter while visible as the camera explores forward, and are deleted from the state once they go out of view. This permits an increase in the number of tracked features per frame from tens to around a hundred. While improving the accuracy of the estimation, it makes computationally infeasible the exhaustive Branch and Bound search performed by standard JCBB for match outlier rejection. As a second contribution that overcomes this problem, we present here a RANSAC-like algorithm that exploits the probabilistic prediction of the filter. This use of prior information makes it possible to reduce the size of the minimal data subset to instantiate a hypothesis to the minimum possible of 1 point, greatly increasing the efficiency of the outlier rejection stage. Experimental results from real image sequences covering trajectories of hundreds of meters are presented and compared against RTK GPS ground truth. Estimation errors are about 1% of the trajectory for trajectories up to 650 metres.